2023
DOI: 10.3390/rs15092279
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of the All-Sky Assimilation of FY-3C and FY-3D MWHS-2 Radiances on Analyses and Forecasts of Typhoon Hagupit

Abstract: With the Microwave Humidity Sounder-2 (MWHS-2)/Fengyun (FY)-3D in operation, this is the first study to evaluate the impact of a joint assimilation of MWHS-2 radiances under all-sky conditions from both the FY-3C and FY-3D satellites on typhoon forecasting within regional areas. In this study, Typhoon Hagupit in 2020 was chosen to investigate the impacts of assimilating MWHS-2 radiances; the forecasting performances of the joint assimilation method were slightly better than the experiments assimilating MWHS-2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 51 publications
(68 reference statements)
0
1
0
Order By: Relevance
“…To evaluate the impact of our new sea surface roughness scheme on the ability of the coupled model to predict sea surface winds, we conduct five sets of experiments, with each set corresponding to a typhoon. These five typhoons landed in mainland China in August 2020 and had severe impacts, resulting in direct economic losses of billions of dollars (Chen et al., 2023). Each experiment starts at 00:00 UTC and extends for 72 hr of forecast.…”
Section: Methodsmentioning
confidence: 99%
“…To evaluate the impact of our new sea surface roughness scheme on the ability of the coupled model to predict sea surface winds, we conduct five sets of experiments, with each set corresponding to a typhoon. These five typhoons landed in mainland China in August 2020 and had severe impacts, resulting in direct economic losses of billions of dollars (Chen et al., 2023). Each experiment starts at 00:00 UTC and extends for 72 hr of forecast.…”
Section: Methodsmentioning
confidence: 99%
“…With the launch of the FY-3D and FY-3C satellites, MWHS2 observations are becoming more crucial to assimilation systems. In their research on assimilating FY-3C MWHS2 data, Chen et al [18,19] made essential contributions. The effect of MWHS2/FY-3C data assimilation using a dynamic emissivity retrieved on precipitation forecast over a complex terrain was examined by Chen et al [18].…”
Section: Introductionmentioning
confidence: 99%
“…Their results indicated that, with the exception of rainfall above 100 mm, employing the dynamic emissivity retrieved from an 89 GHz channel improved the initial fields and the 24 h forecast of intensity and precipitation distribution. The influence of assimilated FY-3C MWHS2 radiance on Typhoon Hagupit forecast was evaluated by Chen et al [19] with FNL analysis data as the background field, and they found that it contributed to the improved analysis of wind fields, relative humidity, and temperature, thus improving the typhoon track and intensity forecast. In addition, the effect of assimilation of MWHS2 data from the FY-3C on the analysis and forecasting of binary typhoons was investigated by Xian et al [20] with FNL reanalysis data as the background field.…”
Section: Introductionmentioning
confidence: 99%